2021
DOI: 10.1177/2332858420986872
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Math Instruction and Student Achievement Through Professional Learning Around the Common Core State Standards in Chicago

Abstract: Existing literature on the impact of Common Core State Standards in Math has shown little benefit, but it has not examined variation in outcomes based on implementation strategies, student subgroups, or outcomes other than test scores. We use a difference-in-differences approach with school fixed effects to compare outcomes in pre- and poststandards years across schools with different levels of participation in professional learning around the standards in the middle grades in Chicago. Postimplementation, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 53 publications
(86 reference statements)
3
11
0
Order By: Relevance
“…A nascent consensus in the literature on the effects of CC on student outcomes is emerging. Consistent with the analysis herein, Loveless (2014Loveless ( , 2015Loveless ( , 2016, Xu and Cepa (2018), Gao andLafortune (2019), andAllensworth et al (2021) all find small positive correlations between the CC and student outcomes. Song et al (2019) find largely negative effects of the CCR standards, which includes CC implementing states, states that made major revisions, and states that never adopted the CC.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A nascent consensus in the literature on the effects of CC on student outcomes is emerging. Consistent with the analysis herein, Loveless (2014Loveless ( , 2015Loveless ( , 2016, Xu and Cepa (2018), Gao andLafortune (2019), andAllensworth et al (2021) all find small positive correlations between the CC and student outcomes. Song et al (2019) find largely negative effects of the CCR standards, which includes CC implementing states, states that made major revisions, and states that never adopted the CC.…”
Section: Discussionsupporting
confidence: 83%
“…Questions about whether the CC content standards improved student outcomes and the size of the relationship has benefitted students remain unresolved (Polikoff, 2017). Studies have found the relationship between CC implementation and student outcomes is mixed (Allensworth et al, 2021;Loveless, 2014Loveless, , 2015Loveless, , 2016Gao & Lafortune, 2019;Song et al, 2019;Xu & Cepa, 2018). In particular, it is unknown whether the CC contributed to the closure of achievement gaps (O'Day, & Smith, 2019;Polikoff, 2017).…”
mentioning
confidence: 99%
“…Learning motivation has a favorable and considerable impact on economic accomplishment, according to the first hypothesis. This conclusion is in line with [7], [8], [9], [24], [25], [26], [27] and [28].…”
Section: The Effect Of Learning Motivation On Economic Learning Achie...supporting
confidence: 84%
“…At the same time, we cannot say with certainty from this analysis that these changes were due to the implementation of the district's plan or the teacher leader model. In another study, we did find significant relationships between the degree to which teachers reported participating in professional learning around the standards and changes in math instruction and math achievement; that study did not examine science (Allensworth et al, 2021).…”
Section: Students Engaged More Frequently In Standards-aligned Practicesmentioning
confidence: 78%